Raising Bilingual Children: an Exploration of Language Ideology and its Practices in an Indonesian Family - Riza Yoga Indriani; Sary Silvhiany; Soni Mirizon (Jurusan Tadris Bahasa Indonesia, 2021)
The role of parents' beliefs or ideology is one of the most important factors in promoting the strategies for encouraging children's bilingual development. This case study examined how the parents' beliefs influenced an effort to practice the languages at home. The data were obtained through observation, in-depth interviews, digital artefacts, and language portrait silhouettes with English-Indonesian bilingual parents, and three children at the age of 6 to 11. Nvivo12 Plus application was used to organize and code the data. The results revealed that the parents believed in the importance of laying language foundations at the golden age as this could lead to shaping confident bilingual children. Findings also highlight the influential factors in parental ideology, i.e. the changing era, parentsâ€™ experience, and the support from the extended family. Although parents chose a non-bilingual school for their children, they could practice English dominantly with children at home with a wide range of strategies.Â Kepercayaan atau ideologi orang tua merupakan salah satu faktor yang paling penting untuk mendukung strategi dan mendorong perkembangan bilingual anak-anak. Studi kasus ini bertujuan untuk meneliti bagaimana kepercayaan orang tua mempengaruhi upaya untuk mempraktekkan bahasa di rumah. Data diperoleh melalui observasi, wawancara mendalam, artefak digital, dan siluet potret bahasa dengan orang tua bilingual Inggris-Indonesia, dan tiga orang anak berusia 6 hingga 11 tahun. Selanjutnya, data tersebut disusun dan dikodekan dengan menggunakan aplikasi Nvivo12 Plus. Hasil penelitian ini menunjukkan bahwa orang tua mempercayai pentingnya meletakkan dasar bahasa pada usia emas karena hal ini dapat membentuk anak bilingual menjadi percaya diri. Hasil ini juga menunjukkan bahwa ada beberapa faktor yang memengaruhi ideologi orang tua, yaitu perubahan zaman, pengalaman orang tua, dan dukungan dari keluarga besar. Meskipun orang tua memilih sekolah non-dwibahasa untuk anak-anak mereka, mereka dapat berlatih bahasa Inggris secara dominan dengan anak-anak di rumah dengan berbagai strategi.